Membina wirausahawan masa depan: Peran inkubator bisnis dalam membentuk niat berwirausaha di perguruan tinggi - Dharmastuti, Christiana Fara; Lembana, Devi Angrahini Anni; Sustaningrum, Rakhdiny (Jurnal Manajemen Maranatha, 2024)
Entrepreneurship plays a pivotal role in national development. Hence, related training is often initiated at the university level to equip students after graduation with entrepreneurial skills through business incubators. This study delves into the crucial role of incubators in fostering entrepreneurial intention among students by considering gender, mentoring, and curriculum design for the learning process. Additionally, it examines the impact of university support in a regulatory way, as well as normatively and cognitively. Moreover, data are collected based on three cohorts of incubator participants across different periods. The findings of this study reveal entrepreneurial intentions based on gender, which is measured by males as the reference category affecting positively. Besides, there is a positive tendency for normative and cognitive environmental support toward these intentions. Unfortunately, mentorship, curriculum program, and regulatory environmental support do not affect these intentions.